Reliable 2D Phase Transitions for Low-Noise and Long-Life Memory Programming - Ding, Keyuan; Li, Tianci; Chen, Bin; Rao, Feng (Frontiers in Nanotechnology, 2021)
Extending cycling endurance and suppressing programming noise of phase-change random-access memory (PCRAM) are the key challenges with respect to the development of non-volatile working memory and high-accuracy neuromorphic computing device. However, the large-scale atomic migration along electrical pulse direction in the unconstrained three-dimensional phase transitions of the phase-change materials (PCMs) induces big resistance fluctuations upon repeated programming and renders the classic PCRAM devices into premature failure with limited cycling endurance. Previous efforts of superlattice-like and superlattice PCM schemes cannot effectively resolve such issues. In this work, we demonstrated that through fine-tuning the sputtering techniques, a phase-change heterostructure (PCH) of Sb2Te3/TiTe2 can be successfully constructed. In contrast to its superlattice-like counterpart with inferior crystal quality, the well-textured PCH architecture ensures the reliable (well-confined) two-dimensional phase transitions, promoting an ultralow-noise and long-life operation of the PCRAM devices. Our study thus provides a useful reference for better manufacturing the PCH architecture and further exploring the excellent device performances and other new physics.